2018
DOI: 10.3390/healthcare6020049
|View full text |Cite
|
Sign up to set email alerts
|

Human Babesiosis Caused by Babesia duncani Has Widespread Distribution across Canada

Abstract: Human babesiosis caused by Babesia duncani is an emerging infectious disease in Canada. This malaria-like illness is brought about by a protozoan parasite infecting red blood cells. Currently, controversy surrounds which tick species are vectors of B. duncani. Since the availability of a serological or molecular test in Canada for B. duncani has been limited, we conducted a seven-year surveillance study (2011–2017) to ascertain the occurrence and geographic distribution of B. duncani infection country-wide. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
0
36
0
1
Order By: Relevance
“…Babesia microti, Babesia duncani, and Babesia divergens are responsible for most cases of babesiosis world-wide (1). Whereas B. microti is endemic in the Northeastern and Midwestern regions of the United States, and has further been reported worldwide, all confirmed cases of B. duncani have been found primarily in the Western United States (2,3). A recent report based on available serological and/or molecular tests has suggested that B. duncani is also widespread in Canada (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Babesia microti, Babesia duncani, and Babesia divergens are responsible for most cases of babesiosis world-wide (1). Whereas B. microti is endemic in the Northeastern and Midwestern regions of the United States, and has further been reported worldwide, all confirmed cases of B. duncani have been found primarily in the Western United States (2,3). A recent report based on available serological and/or molecular tests has suggested that B. duncani is also widespread in Canada (2,3).…”
mentioning
confidence: 99%
“…Whereas B. microti is endemic in the Northeastern and Midwestern regions of the United States, and has further been reported worldwide, all confirmed cases of B. duncani have been found primarily in the Western United States (2,3). A recent report based on available serological and/or molecular tests has suggested that B. duncani is also widespread in Canada (2,3). On the other hand, cases of babesiosis in humans caused by B. divergens have so far been primarily reported in Europe, with some B. divergens-like cases reported in Japan and the United States (4,5).…”
mentioning
confidence: 99%
“…Other recent IFA data also suggest that B. duncani is more widespread in the USA [ 28 , 31 , 34 ] than previously recognized [ 5 , 7 , 22 ]. Human babesiosis caused by B. duncani has also been recently found to be widely distributed in Canada [ 8 ]. While the occurrence of human babesiosis had not been extensively studied in Australia, there is evidence suggesting the indigenous transmission of B. duncani and B. microti in Australia [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human to human transmission of Babesia species can occur through blood transfusion, congenital transmission and organ transplantation [ 3 , 4 , 6 ]. Babesia microti , B. duncani and B. divergens are mainly responsible for human babesiosis in the USA [ 2 , 3 , 4 ] with B. microti and B. duncani considered to be, respectively, more prevalent in the East and West coasts of North America [ 5 , 7 , 8 ]. Babesia microti , B. divergens , B. venatorum and B. crassa are responsible for babesiosis in Eurasia [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Babesia microti and B. duncani [8] are the commonly reported species causing human babesiosis and the infection is confirmed by identification of the organism on Giemsa or Wright's stained blood smears, showing intraerythrocytic tetrads of merozoites, arranged in 'maltese cross' pattern. This appearance is pathognomonic of babesial infection.…”
Section: Introductionmentioning
confidence: 89%